Flexural properties of the epoxy resin filled with single and hybrid carbon nanofillers - Glaskova-Kuzmina, T.; Aniskevich, A.; Zotti, A.; Borriello, A.; Zarrelli, M. (IOP Publishing, 2020)
The aim of this paper was to estimate the effect of moisture and temperature on the flexural properties of the epoxy filled with single and hybrid carbon nanofillers (CNTs and CNFs) and to reveal the most environmentally stable NC. Water absorption at 70 °C until equilibrium moisture content and heating at 70 °C for 4 weeks were followed by freezing at - 20 °C for 8 weeks. Microstructural characterization of optical images revealed homogeneous dispersion of all carbon nanofillers in the epoxy resin at microscale. Positive nanofiller effects were found for sorption, flexural and thermophysical characteristics of the epoxy resin. The most environmentally stable NC was epoxy filled with 0.1 wt. % of CNTs/CNFs hybrid, which had the lowest effect of temperature and moisture on mechanical characteristics, along with the lowest equilibrium water content and diffusivity.
Keywords: flexural properties; epoxy; carbon nanofillers